Accurate interpolation methods for the annual simulation of solar central receiver systems using celestial coordinate system. (1st January 2021) - Richter, P.; Tinnes, J.; Aldenhoff, L.
Highlights: Bicubic interpolation over sun path in equatorial coordinates. Approximation of the efficiency using multi-dimensional approximation methods. Lagrange interpolation over sun path in equatorial coordinates. Calculation of the annual energy production by interpolating the power plant efficiency. Accuracy of 99.9% while using around 40 simulation points. Abstract: Heliostat field layout optimization bases on simulations of the annual energy production. To reduce the computation time of the optimization process, one can try to reduce the number of simulation points of the annual domain, while keeping similar accuracy. For the temporal domain, there exist already different approaches as aggregation of days. To further reduce the number of needed simulation points, in this paper we decouple the power computation from the irradiation, such that we just regard the computation of the power plant efficiency. This time-dependent parameter is transformed into a celestial coordinate system where the solar angle-dependent efficiency will be approximated using suitable multi-dimensional interpolation methods. We distinguish between an accurate approximation of the received annual optical energy and the electrical energy of each moment of a year. These methods are demonstrated for the existing heliostat field layouts PS10 and Gemasolar in Seville, while using realistic weather conditions. With this new approach just around 40 simulation points suffice to reach an accuracy of 99.9% for the received power for smaller power plants as PS10, and for larger plants as Gemasolar . Compared to a state-of-the-art method, this investigation helps to accelerate the simulation by factor three.